Application of armor-type non-metallic electrocatalysts in electrocatalytic reduction of nitrogen oxides to ammonia

By using armor-type non-metallic electrocatalysts in the electrocatalytic reduction of nitrogen oxides to synthesize ammonia, the problems of poor catalyst stability and low effectiveness are solved, efficient and stable ammonia nitrogen synthesis is achieved, and energy consumption and costs are reduced.

CN118791045BActive Publication Date: 2025-01-21CHONGQING TECH & BUSINESS UNIV
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202410818386.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-06-24
Publication Date
2025-01-21
Estimated Expiration
2044-06-24

AI Technical Summary

Technical Problem

The existing electrocatalytic reduction of nitrogen oxide ammonia synthesis technology has the problems of poor catalyst stability and low effect.

Method used

An armor-type non-metallic electrocatalyst is used. The electrocatalyst wraps the tungsten precursor through a hydrothermal reaction and is calcined in a nitrogen atmosphere to form a structure of graphene shell wrapping tungsten trioxide nanosheets, which improves the stability and catalytic activity of the catalytic material.

Benefits of technology

It significantly improves the stability and current efficiency of the catalyst, improves the ammonia nitrogen yield and the overall performance of electrocatalytic reduction of nitrogen oxides to synthesize ammonia, and reduces energy consumption and costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118791045B_ABST
    Figure CN118791045B_ABST
Patent Text Reader

Abstract

The present invention discloses an armor-type non-metallic electrocatalyst for electrocatalytic reduction of nitrogen oxides to synthesize ammonia. The present invention uses glucose as a carbon source, wraps a tungsten precursor through a hydrothermal reaction, and then calcines and graphitizes to form an armor-type structure in which a graphene shell wraps a tungsten trioxide nanosheet, which can achieve a higher ammonia nitrogen yield and current efficiency.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of electrocatalytic reduction of nitrogen oxides to synthesize ammonia, and specifically relates to the application of an armor-type non-metallic electrocatalyst in electrocatalytic reduction of nitrogen oxides to synthesize ammonia. Background Art

[0002] Nitrogen oxides are one of the key factors in the formation of ozone. Research on technologies to reduce nitrogen oxide emissions is very meaningful for controlling ozone pollution.

[0003] At present, electrocatalytic reduction of nitrogen oxides to synthesize ammonia is a cutting-edge new technology for resource-based treatment of nitrogen oxides, which can effectively remove nitrogen oxides generated in power plants, industrial parks and automobile exhaust. In addition, this technology has the characteristics of zero carbon emissions and green synthesis of ammonia nitrogen, and is expected to solve the problems of high energy consumption and high carbon dioxide emissions in existing industrial synthesis ammonia technology. However, this technology still has problems with poor catalyst stability and low effect. Summary of the invention

[0004] In view of this, the object of the present invention is to provide an armor-type non-metallic electrocatalyst for use in electrocatalytic reduction of nitrogen oxides to synthesize ammonia, which can achieve a higher ammonia nitrogen yield and current efficiency.

[0005] In order to achieve the above object, the present invention provides the following technical solutions:

[0006] Application of armor-type non-metallic electrocatalyst in electrocatalytic reduction of nitrogen oxides to synthesize ammonia, the preparation method of the armor-type non-metallic electrocatalyst comprises the following steps:

[0007] (1) dissolving tungstate and citric acid in water, adding glucose and hydrochloric acid solution, stirring and mixing to obtain a reaction solution;

[0008] (2) transferring the reaction solution obtained in step (1) into a high-pressure reactor for hydrothermal reaction, and washing and drying after the reaction to obtain a black powder material;

[0009] (3) calcining the black powder material obtained in step (2) under an inert gas atmosphere to obtain an armor-type non-metallic electrocatalyst having tungsten trioxide nanosheets wrapped in a graphene shell;

[0010] The armor-type non-metallic electrocatalyst is loaded on an electrode substrate to prepare an electrode, which is used as a working electrode in a device for synthesizing ammonia by electrocatalytic reduction of nitrogen oxides.

[0011] As a preferred technical solution, in the armor-type non-metallic electrocatalyst, the thickness of the graphene shell is 5-10 nm, and the width of the nanosheet is 110-180 nm.

[0012] As a preferred technical solution, the hydrothermal reaction temperature in step (2) is 100-200° C., and the reaction time is 12-48 hours.

[0013] As a preferred technical solution, the calcination temperature in step (3) is 200-600°C, the heating rate is 2-10°C / min, and the calcination time is 2-4 hours.

[0014] As a preferred technical solution, the calcination temperature in step (3) is 400-600°C.

[0015] As a preferred technical solution, the calcination temperature in step (3) is 400°C.

[0016] As a preferred technical solution, the loading amount of the armor-type non-metallic electrocatalyst on the electrode substrate is 5-8 mg / cm 2 .

[0017] As a preferred technical solution, the reaction voltage of the electrocatalytic reduction of nitrogen oxides to synthesize ammonia is -0.6 to -1.0 V vs. Ag / AgCl.

[0018] As a preferred technical solution, the reaction voltage of the electrocatalytic reduction of nitrogen oxides to synthesize ammonia is -0.8Vvs.Ag / AgCl.

[0019] The beneficial effects of the present invention are:

[0020] The present invention uses glucose as a carbon source, wraps a tungsten precursor through a hydrothermal reaction, and then calcines and graphitizes to form an armor-like structure in which a graphene shell wraps a tungsten trioxide nanosheet; the graphene shell can effectively resist the corrosion of nitrogen oxides and other acidic impurities, significantly improve the stability of the catalytic material, and enhance the applicability of the electrode material, so that it can also exhibit a more efficient catalytic activity under a more complex environmental system; at the same time, the tungsten trioxide core can regulate the electronic structure of the graphene shell through the interfacial electron penetration effect, enhance the adsorption and activation of nitrogen oxides, improve the selectivity of the reaction, inhibit the occurrence of hydrogen evolution reaction, improve the current efficiency of electrocatalytic nitrogen oxide synthesis of ammonia, and reduce energy consumption and cost. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] In order to make the purpose, technical solution and beneficial effects of the present invention clearer, the present invention provides the following drawings for illustration:

[0022] Figure 1 This is a transmission electron microscopy image of the armor-type non-metallic electrocatalyst WO3@GR1 prepared in Example 1.

[0023] Figure 2 This is a transmission electron microscopy image of the armor-type non-metallic electrocatalyst WO3@GR2 prepared in Example 1.

[0024] Figure 3 This is a transmission electron microscopy image of the armor-type non-metallic electrocatalyst WO3@GR3 prepared in Example 1.

[0025] Figure 4 This is a transmission electron microscopy image of the armor-type non-metallic electrocatalyst WO3@GR4 prepared in Example 1.

[0026] Figure 5 This is the X-ray diffraction pattern of the armor-type non-metallic electrocatalyst WO3@GR2 prepared in Example 1.

[0027] Figure 6 This is the current efficiency (FE) diagram of the electrocatalytic reduction of nitrogen oxides to synthesize ammonia by the armor-type non-metallic electrocatalyst WO3@GR1-4 prepared at different calcination temperatures in Example 1.

[0028] Figure 7 This is the current efficiency (FE) diagram of the electrocatalytic reduction of nitrogen oxides to synthesize ammonia by WO3@GR2 of Example 1 and WO3, GP, rGO and BC of Comparative Example 1.

[0029] Figure 8 Figure 2 shows the current efficiency (FE) of armor-type non-metallic electrocatalyst WO3@GR2 under different applied voltages.

[0030] Fig. 9 This is the current efficiency (FE) diagram of the armor-type non-metallic electrocatalyst WO3@GR2 prepared in Example 3 after 100 hours of continuous reaction. DETAILED DESCRIPTION

[0031] The present invention is further described below in conjunction with the accompanying drawings and specific embodiments so that those skilled in the art can better understand the present invention and implement it, but the embodiments are not intended to limit the present invention.

[0032] Example 1

[0033] (1) Dissolve 330 mg of sodium tungstate dihydrate and 288 mg of citric acid in 30 mL of water, add 2000 mg of glucose monohydrate and stir vigorously for 10 minutes, then add 3 mL of 1:1 hydrochloric acid and continue to stir vigorously for 30 minutes;

[0034] (2) The above solution was transferred to a high-pressure reactor and subjected to a hydrothermal reaction at 120° C. for 24 hours. After the reaction, the solution was washed with water and ethanol several times and dried in a vacuum drying oven at 60° C. overnight to obtain a black powder.

[0035] (3) Under a nitrogen atmosphere, the black powder was placed in a tube furnace, heated to 200, 400, 600 and 800 °C at a rate of 2 °C / min, and calcined for 2 h to finally obtain a black armor-type non-metallic electrocatalyst WO3@GR (labeled WO3@GR1-4 in sequence).

[0036] (4) Add 40 mg of WO3@GR1-4 to a solution with a ratio of ethanol: isopropanol: nafion of 4:1:0.01 to prepare an ink solution; apply the ink droplets to a 6 cm 2 The super-hydrophobic carbon paper was placed in a vacuum drying oven at 60°C and dried for 12 hours to prepare an electrode;

[0037] (5) The electrode was loaded into a commercial gas diffusion electrode reactor, a voltage of -0.8 V vs. Ag / AgCl was applied, the electrolyte was a 0.1 mol / L dilute sulfuric acid solution, and a nitrogen oxide-containing gas was introduced at a flow rate of 5 mL / min to perform an electrocatalytic reduction of nitrogen oxides to synthesize ammonia. The reaction time was 1 hour.

[0038] The current efficiency (FE) is calculated as follows:

[0039]

[0040] Where F is the Faraday constant (96500C mol -1 ), Q is the charge consumed by the reaction, V is the reaction volume, C NH3 is the concentration of ammonia nitrogen produced by the reaction.

[0041] Figures 1 to 4 Transmission electron micrographs of armor-type non-metal electrocatalysts WO3@GR1-4 prepared in Example 1, wherein the width of WO3@GR1 (calcined at 200°C) is 144.9nm, and the thickness of the graphene shell is 7.4nm; the width of WO3@GR2 (calcined at 400°C) is 114.8nm, and the thickness of the graphene shell is 6.3nm; the width of WO3@GR3 (calcined at 600°C) is 142.2nm, and the thickness of the graphene shell is 5.0nm. The transmission electron micrograph of WO3@GR4 (calcined at 800°C) shows that the flaky particles are agglomerated.

[0042] The present invention has found that when the calcination temperature is low, the degree of graphitization is insufficient, resulting in instability of the carbon layer material. As the calcination temperature increases, the degree of graphitization of the surface carbon layer increases, and the stability of the carbon layer is enhanced. However, as the temperature increases, the carbon layer will be gradually burned and thinned. If the temperature is too high and the carbon layer is too thin, the protection of the inner core WO3 is insufficient, which will cause WO3 to agglomerate and dissolve in the reaction, reducing the effect. The preferred calcination temperature is 400-600°C, and the most preferred calcination temperature is 400°C.

[0043] Figure 5 This is the X-ray diffraction pattern of the armor-type non-metallic electrocatalyst WO3@GR2 prepared in Example 1. The peaks in the figure are all diffraction peaks of tungsten trioxide.

[0044] Figure 6 This is a current efficiency diagram of the electrocatalytic reduction of nitrogen oxides to synthesize ammonia by the armor-type non-metallic electrocatalysts WO3@GR1-4 prepared at different calcination temperatures in Example 1, among which the armor-type non-metallic electrocatalyst WO3@GR2 prepared at a calcination temperature of 400°C has the highest current efficiency.

[0045] Comparative Example 1

[0046] (1) 40 mg of tungsten trioxide (WO3), redox graphene (rGO), carbon black (BC) and commercial graphite (GP) were added to a solution with a ratio of ethanol: isopropanol: nafion of 4:1:0.01 to prepare an ink solution; the ink droplets were applied to a 6 cm 2 The super-hydrophobic carbon paper was placed in a vacuum drying oven at 60°C and dried for 12 hours to prepare an electrode;

[0047] (2) The electrode was loaded into a commercial gas diffusion electrode reactor, a voltage of -0.8 V vs. Ag / AgCl was applied, the electrolyte was a 0.1 mol / L dilute sulfuric acid solution, and a nitrogen oxide-containing gas was introduced at a flow rate of 5 mL / min to perform an electrocatalytic reduction of nitrogen oxides to synthesize ammonia. The reaction time was 1 hour.

[0048] The current efficiency (FE) is calculated as follows:

[0049]

[0050] Where F is the Faraday constant (96500C mol -1 ), Q is the charge consumed by the reaction, V is the reaction volume, C NH3 is the concentration of ammonia nitrogen produced by the reaction.

[0051] Figure 7 This is a current efficiency (FE) graph of the electrocatalytic reduction of nitrogen oxides to synthesize ammonia by WO3@GR2 of Example 1 and WO3, rGO, BC and GP of Comparative Example 1. Among them, the current efficiency of the armor-type non-metallic electrocatalyst WO3@GR2 is the highest, proving that the catalytic effect of the armor-type non-metallic electrocatalyst is better than that of ordinary carbon-based materials (graphite, carbon black and redox graphene).

[0052] Example 2

[0053] (1) Dissolve 330 mg of sodium tungstate dihydrate and 288 mg of citric acid in 30 mL of water, add 2000 mg of glucose monohydrate and stir vigorously for 10 minutes, then add 3 mL of 1:1 hydrochloric acid and continue to stir vigorously for 30 minutes;

[0054] (2) The above solution was transferred to a high-pressure reactor and subjected to a hydrothermal reaction at 120° C. for 24 hours. After the reaction, the solution was washed with water and ethanol several times and dried in a vacuum drying oven at 60° C. overnight to obtain a black powder.

[0055] (3) Under a nitrogen atmosphere, the black powder was placed in a tube furnace, heated to 400 °C at a rate of 2 °C / min, and calcined for 2 h to finally obtain a black armor-type non-metallic electrocatalyst WO3@GR2.

[0056] (4) Add 40 mg of WO3@GR2 to a solution with a ratio of ethanol: isopropanol: nafion of 4:1:0.01 to prepare an ink solution; apply the ink droplets to a 6 cm 2 The super-hydrophobic carbon paper was placed in a vacuum drying oven at 60°C and dried for 12 hours to prepare an electrode;

[0057] (5) The electrode was loaded into a commercial gas diffusion electrode reactor, and voltages of -0.6, -0.7, -0.8, -0.9 and -1.0 V vs. Ag / AgCl were applied, respectively. The electrolyte was a 0.1 mol / L dilute sulfuric acid solution. A nitrogen oxide-containing gas was introduced at a flow rate of 5 mL / min to carry out the electrocatalytic reduction of nitrogen oxides to synthesize ammonia. The reaction time was 1 hour.

[0058] The current efficiency (FE) is calculated as follows:

[0059]

[0060] Where F is the Faraday constant (96500C mol -1 ), Q is the charge consumed by the reaction, V is the reaction volume, C NH3 is the concentration of ammonia nitrogen produced by the reaction.

[0061] Figure 8 This is the current efficiency diagram of the armor-type non-metallic electrocatalyst WO3@GR2 under different applied voltages, among which the current efficiency is the highest when the applied voltage is -0.8V vs.Ag / AgCl.

[0062] Example 3

[0063] (1) Dissolve 330 mg of sodium tungstate dihydrate and 288 mg of citric acid in 30 mL of water, add 2000 mg of glucose monohydrate and stir vigorously for 10 minutes, then add 3 mL of 1:1 hydrochloric acid and continue to stir vigorously for 30 minutes;

[0064] (2) The above solution was transferred to a high-pressure reactor and subjected to a hydrothermal reaction at 120° C. for 24 hours. After the reaction, the solution was washed with water and ethanol several times and dried in a vacuum drying oven at 60° C. overnight to obtain a black powder.

[0065] (3) Under a nitrogen atmosphere, the black powder was placed in a tube furnace, heated to 400 °C at a rate of 2 °C / min, and calcined for 2 h to finally obtain a black armor-type non-metallic electrocatalyst WO3@GR2.

[0066] (4) Add 40 mg of WO3@GR2 to a solution with a ratio of ethanol: isopropanol: nafion of 4:1:0.01 to prepare an ink solution; apply the ink droplets to a 6 cm 2 The super-hydrophobic carbon paper was placed in a vacuum drying oven at 60°C and dried for 12 hours to prepare an electrode;

[0067] (5) The electrode was loaded into a commercial gas diffusion electrode reactor. The reaction device was a continuous flow reactor. The applied voltage was -0.8 V vs. Ag / AgCl. The electrolyte was a 0.1 mol / L dilute sulfuric acid solution. A nitrogen oxide-containing gas was introduced at a flow rate of 5 mL / min to carry out an electrocatalytic reduction of nitrogen oxides to synthesize ammonia. The reaction time was 100 hours.

[0068] The current efficiency (FE) is calculated as follows:

[0069]

[0070] Where F is the Faraday constant (96500C mol -1 ), Q is the charge consumed by the reaction, V is the volume involved in the reaction in the continuous flow system, C NH3 is the concentration of ammonia nitrogen produced by the reaction.

[0071] Fig. 9 This is the current efficiency diagram of the armor-type non-metallic electrocatalyst WO3@GR2 prepared in Example 3 after 100 hours of continuous reaction. The current efficiency is basically maintained at 91.1%, proving that the armor-type non-metallic electrocatalyst has good stability and can be used for a long time.

[0072] The above-described embodiments are only preferred embodiments for fully illustrating the present invention, and the protection scope of the present invention is not limited thereto. Equivalent substitutions or changes made by those skilled in the art based on the present invention are within the protection scope of the present invention. The protection scope of the present invention shall be subject to the claims.

Claims

1. Application of armor-type non-metallic electrocatalyst in electrocatalytic reduction of nitrogen oxides to synthesize ammonia, characterized in that: The preparation method of the armor-type non-metallic electrocatalyst comprises the following steps: (1) Dissolve tungstate and citric acid in water, add glucose and hydrochloric acid solution, stir and mix to obtain a reaction solution; (2) transferring the reaction solution obtained in step (1) into a high-pressure reactor for hydrothermal reaction, and washing and drying after the reaction to obtain a black powder material; (3) calcining the black powder material obtained in step (2) under an inert gas atmosphere to obtain an armor-type non-metallic electrocatalyst having a graphene shell wrapped around tungsten trioxide nanosheets; the calcination temperature in step (3) is 200-600° C., the heating rate is 2-10° C. / min, and the calcination time is 2-4 hours; The armor-type non-metallic electrocatalyst is loaded on an electrode substrate to prepare an electrode, which is used as a working electrode in a device for synthesizing ammonia by electrocatalytic reduction of nitrogen oxides.

2. The use of the armor-type non-metallic electrocatalyst according to claim 1 in electrocatalytic reduction of nitrogen oxides to synthesize ammonia, characterized in that: In the armor-type non-metallic electrocatalyst, the thickness of the graphene shell is 5-10 nm, and the width of the nanosheet is 110-180 nm.

3. The use of the armor-type non-metallic electrocatalyst according to claim 1 in the electrocatalytic reduction of nitrogen oxides to synthesize ammonia, characterized in that: The hydrothermal reaction temperature in step (2) is 100-200° C., and the reaction time is 12-48 hours.

4. The use of the armor-type non-metallic electrocatalyst according to claim 1 in the electrocatalytic reduction of nitrogen oxides to synthesize ammonia, characterized in that: The calcination temperature in step (3) is 400-600°C.

5. The use of the armor-type non-metallic electrocatalyst according to claim 4 in the electrocatalytic reduction of nitrogen oxides to synthesize ammonia, characterized in that: The calcination temperature in step (3) is 400°C.

6. Use of the armor-type non-metallic electrocatalyst according to any one of claims 1 to 5 in electrocatalytic reduction of nitrogen oxides to synthesize ammonia, characterized in that: The loading amount of the armor-type non-metal electrocatalyst on the electrode substrate is 5-8 mg / cm 2 .

7. Use of the armor-type non-metallic electrocatalyst according to any one of claims 1 to 5 in electrocatalytic reduction of nitrogen oxides to synthesize ammonia, characterized in that: The reaction voltage of the electrocatalytic reduction of nitrogen oxides to synthesize ammonia is -0.6 to -1.0 V vs. Ag / AgCl.

8. The use of the armor-type non-metallic electrocatalyst according to claim 7 in electrocatalytic reduction of nitrogen oxides to synthesize ammonia, characterized in that: The reaction voltage of the electrocatalytic reduction of nitrogen oxides to synthesize ammonia is -0.8 V vs. Ag / AgCl.

Citation Information

Patent Citations

  • Preparation method of defect foam graphene loaded transition metal monatomic catalyst

    CN113215597A